1998
DOI: 10.1046/j.1365-2052.1998.296380.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial control region and 12S rRNA variation in Przewalski’s horse (Equus przewalskii)

Abstract: Variation in the control region and the 12S rRNA gene of all surviving mitochondrial lineages of Przewalski's horse was investigated. Variation is low despite the present day population being descended from 13 individuals probably representing animals from three different regions of its range. Phylogenetic comparison of these sequences, with sequences for the domestic horse, does not resolve the ancestral status of either horse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 0 publications
3
41
2
Order By: Relevance
“…2). This finding is in agreement with the observation that virtually all Przewalski's horse control region haplotypes belong to haplogroup F, with one notable exception (AF055879) (23). Recently, four complete Przewalski mtDNAs were published (24).…”
Section: Resultssupporting
confidence: 81%
“…2). This finding is in agreement with the observation that virtually all Przewalski's horse control region haplotypes belong to haplogroup F, with one notable exception (AF055879) (23). Recently, four complete Przewalski mtDNAs were published (24).…”
Section: Resultssupporting
confidence: 81%
“…According to studbook records, four mitochondrial lineages survived, and a sequencing study (4) showed that only two mtDNA types exist in these four lineages. However, in the Przewalski's horses' sequences we found three mtDNA types, the third in the data of Ishida et al (10).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed therefore that Przewalski horses are not ancestral to modern domestic horses 23,30 . However, the Przewalski haplotypes do fall within the large diversity of modern horse mtDNA 14,15,17,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of Przewalski's horse to modern domestic horses remains controversial 9,11,17,[28][29][30] . Przewalski horses are generally viewed as either the last surviving wild-horse population, or a feral-horse population derived from a primitive domestic lineage.…”
Section: Discussionmentioning
confidence: 99%